2007
DOI: 10.1080/02699050701785054
|View full text |Cite
|
Sign up to set email alerts
|

Brain injury in a forensic psychiatry population

Abstract: This study provides evidence to support routine screening for a history of TBI in forensic psychiatry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 24 publications
3
46
0
Order By: Relevance
“…Among studies looking at the prevalence of TBI among females offenders (Bogner & Corrigan, 2009; Brewer‐Smyth et al., 2004; Colantonio et al., 2007, 2014; Diamond, Harzke, Magaletta, Cummins, & Frankowski, 2007; Ferguson et al., 2012; Gunter et al., 2009; Hawley & Maden, 2003; Hux et al., 1998; Lewis, Pincus, Feldman, Jackson, & Bard, 1986; Perron & Howard, 2008; Sarapata, Herrmann, Johnson, & Aycock, 1998; Slaughter, Fann, & Ehde, 2003), the rates vary from 9.5% (Perron & Howard, 2008) to 100% (Lewis et al., 1986). A rate of 100% was found in a very small sample of two women.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Among studies looking at the prevalence of TBI among females offenders (Bogner & Corrigan, 2009; Brewer‐Smyth et al., 2004; Colantonio et al., 2007, 2014; Diamond, Harzke, Magaletta, Cummins, & Frankowski, 2007; Ferguson et al., 2012; Gunter et al., 2009; Hawley & Maden, 2003; Hux et al., 1998; Lewis, Pincus, Feldman, Jackson, & Bard, 1986; Perron & Howard, 2008; Sarapata, Herrmann, Johnson, & Aycock, 1998; Slaughter, Fann, & Ehde, 2003), the rates vary from 9.5% (Perron & Howard, 2008) to 100% (Lewis et al., 1986). A rate of 100% was found in a very small sample of two women.…”
Section: Discussionmentioning
confidence: 99%
“…The rate of 21% found in our study is thus lower than previous findings. There are several possible reasons for this result: definitions of TBI are not always the same and lead to differences in reported rates (e.g., some studies define TBI as any head injury, whereas some consider TBI only if there has been a LOC); the populations studied are not similar and the purposes of the studies differ (e.g., in Colantonio's study (Colantonio et al., 2007)), the aim was to evaluate the prevalence of TBI among a forensic psychiatry population).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, the majority of studies appear to indicate the rate of TBI may be significantly higher than that found in the general population (Magaletta, Diamond, Dietz, & Jahnke, 2006;Colantonio, Stamenova, Abramowitz, Clarke, & Christensen, 2007). Among research studies with relatively small samples, rates of TBI have ranged from 8% for a group of 13 non-violent offenders (Leon-Carrion & Ramos, 2003) up to 100% for a sample of 15 inmates on death row (Lewis et al, 1986).…”
Section: Prevalence In Incarcerated Populationsmentioning
confidence: 99%